Finansowanie gminnego szkolnictwa obowiązkowego z bezzwrotnych źródeł pozabudżetowych - Gońda, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
State budget resources and communal own revenues provided to finance compulsory schools expenditures are often not sufficient. Therefore it is necessary to obtain incomes for financing educational spendings from additional sources. The aim of the article is to present the possibilities of obtaining non-returnable funds from non-budgetary sources. Additionally, the author attempts to find out 1) the role of the local authorities and headteachers in the process of looking for additional funds for the communal schools 2) the factors limiting the possibilities of obtaining these funds. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 373-385